Digital Marketing and Artificial Intelligence on Purchasing Decision in the Shopee App - Zhensen; Dedy Lazuardi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
In this digital era, the role of e-commerce, especially Shopee, has grown so fast and has an important role in people's daily lives, the features created to make it easier for people to make purchases have encouraged people to continue making purchases. This study aims to determine whether digital marketing and artificial intelligence have a significant effect on purchasing decisions in the Shopee application. This study uses quantitative data with the population being people in the Medan Baru area totaling 36,191. The sample was obtained using the slovin formula as many as 100 respondents. The data collection technique uses judgmental or purposive sampling. The results showed that digital marketing (X1) and artificial intelligence (X2) had a positive and significant effect partially or simultaneously on purchasing decisions (Y). The results of the coefficient of determination (R2) test show that there is a relationship between the variables digital marketing (X1) and artificial intelligence (X2) with purchasing decisions (Y) in the Shopee application. Shopee is expected to utilize artificial intelligence (X2) as a customer assistance tool and maintain digital marketing (X1). This involves various aspects of technology in the Shopee application with the aim of increasing customer convenience and increasing company marketing.